Ground beetles of the subfamily Lebiinae (Carabidae) of Guinea-Bissau: description of three new species and faunistic notes - Serrano, Artur R. M. (Zootaxa, 2024)
Three new species of ground beetles belonging to the genera Arsinoe Laporte de Castelnau, 1835, Dontolobus Basilewsky, 1970 and Lasiocera Dejean, 1831 (Coleoptera, Carabidae, Lebiinae), respectively, from Guinea-Bissau are described: Arsinoe aguiari n. sp., Dontolobus bivari n. sp. and Lasiocera schwarzi n. sp., together with illustrations of their habitus and aedeagus. Moreover, an annotated checklist of 35 species and subspecies of Lebiinae is provided, including data on general distribution, new country and new distribution records at country level. The list includes novel information from one entomological mission to that country carried out in 2009 and corrigenda data on previous published species. Further, dichotomic keys are made available for the identification of the Guinea-Bissau species of the Arsinoe, Dontolobus and Lasiocera genera. Some considerations on the distribution and conservation status of these beetles in Guinea-Bissau are also presented.